SWOT Analysis of Human Resource Management with Graduate Competence as an Intervening Variable at the HRDA for Transportation, Technical Implementation Unit, West Sumatra Maritime Polytechnic - Syamsyir, Syamsyir; M. Havidz Aima (Siber Nusantara Review & Yayasan Sinergi Inovasi Bersama (SIBER), 2024)
Human resources (HR) are crucial for vocational education institutions like the West Sumatra Maritime Polytechnic to produce competent graduates ready for the maritime industry. However, evidence indicates that the graduates' skills do not meet industry standards. This study aims to analyze human resource management at the West Sumatra Maritime Polytechnic using SWOT analysis. Data collection methods included observation, documentation studies, and interviews. The analysis results show that the West Sumatra Maritime Polytechnic has strengths in experienced instructors and adequate facilities, but it also has weaknesses in ineffective recruitment and training systems. Opportunities arise from government support, partnerships with the industry, and competition with other educational institutions. Considering the SWOT matrix, collaboration with companies is the best strategy to enhance business outcomes.